Pengaruh Media Sosial Sehat Terhadap Keberhasilan Ujian Sekolah Ditinjau dari Undang-Undang No. 19 Tahun 2016 tentang Perubahan Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Arista Candra Irawati; Khifni Kafa Rufaida (Multimatrix, 2018)
Abstrak - Globalization has brought significant change toward social media communication as online media. Freedom and powerfull social media user participates, shares, and creates the content. Therefore, It is important to find a better content for students whose prepare final examination. Social media should become a motivation to for students to find educational content, nevertheless a negative aspect more popular. The paradox, then, emerges when the bad side finally meet internet regulation, UU ITE 2016, which restrict internet freedom. A regretful accident could be ignorance when the pupils of SMK Perintis 29 Ungaran have awareness and knowledge about the rules, compared with a breaking rule incident in SMK at Medan.Keywords: social media, final examination, success